CREATING INTRAPRENEURSHIP AS AN AREA OF CORPORATE ENTREPRENEURSHIP - Nowacka, Urszula; Głębocki, Rafał; Gil, Alina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article focuses on the characteristics of intrapreneurship as an area of corporate entrepreneurship. Attention was paid to the essence and importance of intrapreneurship in the organization. Then, based on the analysis of activities supporting intrapreneurship undertaken in an international corporation of the banking sector and literature research on this subject, a model was developed to stimulate the creation of intrapreneurship within large organizations. The tools used in the model are divided into tools from the category of people management (soft) and tools related to working methods.